2000
DOI: 10.1161/01.res.86.9.952
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 Induces Endothelial Cell Sprouting Through the Activation of Focal Adhesion Kinase and Plasmin Secretion

Abstract: Abstract-Angiopoietin-1 (Ang1) is a strong inducer of endothelial cell sprouting, which is a first step in both angiogenesis and neovascularization. We examined the mechanisms underlying Ang1-induced cell sprouting using porcine pulmonary artery endothelial cells. Ang1 induced the nondirectional and directional migration of endothelial cells mediated through the Tie2 but not the Tie1 receptor. Ang1 induced tyrosine phosphorylation of p125 FAK , and this phosphorylation was dependent on phosphatidylinositol (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
189
2
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(201 citation statements)
references
References 32 publications
6
189
2
4
Order By: Relevance
“…5 Ang1 has also been shown to induce postnatal angiogenesis in a variety of experimental models. In cultured cells, Ang1 alone induced EC chemotaxis, 8,14,15,30 capillary-like tube formation 9 -11 and sprouting angiogenesis, 30 and enhanced EC survival. 11,20 In vivo reports have shown that Ang1 is unable to induce angiogenesis alone, but potentiated the angiogenic response to VEGF.…”
Section: Discussionmentioning
confidence: 98%
“…5 Ang1 has also been shown to induce postnatal angiogenesis in a variety of experimental models. In cultured cells, Ang1 alone induced EC chemotaxis, 8,14,15,30 capillary-like tube formation 9 -11 and sprouting angiogenesis, 30 and enhanced EC survival. 11,20 In vivo reports have shown that Ang1 is unable to induce angiogenesis alone, but potentiated the angiogenic response to VEGF.…”
Section: Discussionmentioning
confidence: 98%
“…Angiopoietin-1 appears to potentiate the effects of VEGF in mouse corneal assays (Asahara et al, 1998). Tie-2, the receptor for this ligand, is essential for vascular development during late organogenesis (Puri et al, 1999), and has been found to mediate angiopoietin-1 induced endothelial cell migration (Kim et al, 2000). Addition of soluble tie-2 to explants attenuated tube formation, and when added with either anti-bFGF or anti-VEGF virtually negated tube formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence suggesting that Ang1 may stimulate chemotaxis, tubule formation, and vascular sprouting and hence act as a proangiogenic agent. 9,[13][14][15] In fact, transgenic mice with increased expression of Ang1 in skin under control of the keratin-14 promoter show a moderate increase in number and a large increase in diameter of dermal vessels, demonstrating that Ang1 is proangiogenic in skin. 16 Transgenic mice with increased expression of VEGF in skin showed a large increase in leaky dermal vessels, and double transgenic mice with coexpression of Ang1 and VEGF had an additive effect on angiogenesis, but the vessels did not leak spontaneously and were resistant to inflammation-induced leakage.…”
Section: Introductionmentioning
confidence: 99%